Politik Dinasti Di Indonesia : Tinjauan Kritis Terhadap Penerapan Demokrasi Di Era Kepemimpinan Presiden Jokowi - Asitha Dewi Mustika Syanur; Ida Bagus Shantih A. W.; Lucy Afrilia (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
The aim of the research is to reveal dynastic politics and the implementation of democracy in the era of President Jokowi's leadership. The 1945 Constitution of the Republic of Indonesia, explicitly recognizes that the form of the Unitary State of the Republic of Indonesia adopts a democratic system. In reality, dynastic politics or political dynasties have developed and are considered a violation of democratic ethics in Indonesia. All efforts and strategies made by the ruling parties to assign positions based on